THE ICONOGRAPHIC ANALYSIS OF THE EMBELLISHMENTS, MADE WITH PRESSURE RELIEF TECHNIQUE, ON TWO STORAGE JARS IN KARS MUSEUM DATED TO GREAT SELJUKS ERA - Yusuf ÇETİN (Fırat University, 2019)
Great Seljuks established a great empire in a very short time by appearing in Iran-based stage of history at the end of X century. The Seljuks, who created a brand new style under the name of “Seljuk Style” by combining the Pre-Islamic Turkish art traditions with the local art in the region where they expanded, created a sense of art which would last for centuries by spreading this style through every corner of Islamic geography. Figure-ornamented ceramics and tiles constitute one of the fields in which this style which show many characteristics in several art fields can be best observed. 48 km from the city centre of Kars, located in the eastern border of Turkey by Arpaçay stand, a medieval settlement Ani has become one of the prominent culture-art centres of Medieval Turkic-Islamic art via its walls, palace, mosques and civil architecture structures after its conquest by the Great Seljuk Sultan Alpaslan in 1064. In Ani archaeological excavation which was first displayed in 1965 and second in 2008 at Kars Museum, two unglazed ceramic storage jars with red and grey earthenware and a red slip, which were found in the layers from Turkic period and dated to XII-XIII century Seljuk period, attract attention for the embellishments on them. On the waists of the storage jars, interrelated animals around the jars in a line, human figures and various symbols, which are made by pressure relief technique, are repeatedly depicted in a stage flow. When examined, the formal characteristics and iconographic analysis of these embellishments, whose source traces to Pre-Islamic Middle Asian Turkic art periods, while unfold a prosperous and mystic world on one hand, make up significant hints about the relation between Pre-Islamic Middle Asian Turkic art and Post-Islamic Turkic art, on the other.